Successful termination of undesirable pregnancy during first trimester in mare - Kumar, Sajjan; Pal, Yash; Legha, Ram Avatar; Talluri, Thirumala Rao (The Indian Journal of Animal Reproduction, 2022)
A seven-year-old Marwari mare that was routinely used in semen collection programme was mismated by a fertile stallion.  The mare was active and alert and all the clinical and hematological parameters were observed to be normal at the time of examination of pregnancy. Rectal examination of the mare through ultrasonography on day 15 revealed an embryonic vesicle confirming the pregnancy.   Initially, the pregnancy was tried to terminate with prostaglandins and prostaglandins in combination with oxytocin, but, the pregnancy persisted and the levels of progesterone (P4) were observed to be elevated.  Manual crushing for pregnancy termination was also tried but proved unsuccessful. Uterine lavage by infusing the weak iodine solution in combination with Ringer’s lactate helped in flushing out the conceptus and the levels of P4 were also observed to decrease after the expulsion and the uterus was also found to be devoidof any fluid. The mare showed uneventful recovery and exhibited regular cycles later on and did not show up any abnormalities in conceiving in the consecutive cycles.
Keywords: Mare; Pregnancy; Termination; Prostaglandin; Progesterone